Pendidikan Islam Masa Khulafaur Rasyidin dan Kontekstualisasinya Pada Pendidikan Islam Masa Kini - Utomo Rachman; Agus Widodo (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to examine the concept of Islamic education during the khulafaur rasyidin era and its contextualization in dealing with the problems of contemporary Islamic education. This study used a qualitative method with a library research approach. The researcher collects literature that discusses the concept of Islamic education during the khulafaur rasyidin era and the problems of contemporary education. The results of this study indicate that education during the khulafaur rasyidin period as a whole was almost the same as that during the Prophet's era, coupled with several developments that occurred in accordance with the conditions and needs of the Muslim community at that time. By contextualizing this, it is hoped that all parties responsible for education can consider it to take steps in overcoming the problems of Islamic education.